Pengaruh Kepemimpinan dan Lingkungan Kerja terhadap Kualitas Kerja : Studi Kasus pada MAS YIA Panembong Tasikmalaya - Ita Sukmawati; Rita Tri Yusnita; Arga Sutrisna (CV. Ulil Albab Corp, 2022)
This research is conducted by the objective to know the effects of leadership and work environment on the quality of work on the teaching staff of MAS YIA Panembong Tasikmalaya. The method used in this study is a quantitative approach with the causality method. Data collection techniues were obtained directly questionnaires distributed to 25 respondents who were teaching staff of MAS YIA Panembong Tasikmalaya. the data analysis tool used in this study is regression analysis. Based on the results of the study it can be seen that: (1)The picture of leadership in MAS YIA Panembong Tasikmalaya has been very good, the work environment has also looked good, and the quality of work of the teaching staff has been very good. (2) There is an influence of leadership and work environment on the quality of work of teaching staff in MAS YIA Panembong Tasikmalaya which is positive and significantly. (3) There is an influence of leadership on the quality of work of teaching staff in MAS YIA Panembong Tasikmalaya which is positive but not significantly. (4) There is an influence of work environment on the quality of work of the teaching staff in MAS YIA Panembong Tasikmalaya which is positive and significantly.